Linking the Swiss Emissions Trading System with the EU ETS: Economic Effects of Regulatory Design Alternatives - Frank Vöhringer (Swiss Journal of Economics and Statistics, 2012)
The Swiss government intends to link the Swiss Emissions Trading System to the EU ETS after 2012. Employing GENESwIS, a dynamic computable general equilibrium (CGE) model of the Swiss economy, we investigate the macroeconomic and sectoral effects of a post-2012 Swiss ETS with linking to the EU ETS. It is the first such CGE analysis for Switzerland with disaggregated sectors according to magnitude of CO2 emissions from installations, which allows distinguishing ETS installations from non-ETS installations in the same sector. The reference scenario represents the announced post-2012 Swiss climate policy without ETS, implying a GHG emissions target for 2020 of -20% with respect to 1990. In the ETS policy scenarios, regulatory issues include participation thresholds and the share of auctioned permits. We show that the Swiss ETS reduction targets are not ambitious when declining baseline emissions are assumed. Thus, most ETS installations profit from an ETS, while non-ETS sectors have to reduce more emissions (and pay a higher CO2 tax). In the context of the simulated Swiss ETS scenarios, we find that distributional consequences of regulatory choices are far more important than efficiency considerations.
Keywords: Q54; Q58; D58; 330; Emissions trading system; climate policy; energy policy; Switzerland; computable general equilibrium model